A "cough induced" pelvic fracture as the first sign of a malignant neoplasm. (2015) - Sharma, N.; Sidhu, M.; Simpson, D.
Highlights: Case report of 80y sustaining pathological pelvic fracture after coughing. Patient had been investigated extensively 6 months before for weight loss. All results were inconclusive. Further investigations reveal synchronous primary malignancies of the stomach and lung. Recommend regular follow up for patients investigated with unexplained weight-loss with inconclusive results, but with a high index of suspicion for malignancy. Abstract: Introduction: We report a case of a "cough induced" pelvic fracture. There has been no prior documentation of this. Presentation of case report: An eighty-year old patient presented to the emergency department after a severe coughing fit and subsequent inability to mobilize. A loud crunch was noted arising from the hip at the time of coughing. Radiographs demonstrated a left ilium fracture with metastatic deposits by computerized tomography. The patient had been investigated extensively six months before presentation for weight loss, but results were inconclusive. Investigations following admission (oesophagogastroduodenoscopy, bronchoscopy, magnetic-resonance, computerized-tomography) confirmed a grade-4 non-small cell lung, and poorly differentiated gastric cancers with secondary metastases to bone and liver. Discusssion: Despite this patient having being investigated extensively for a presumed neoplasm the results of which, at the time were inconclusive, she presented six-months later with lung cancer and gross metastasis to the stomach, liver and bone, not amenable for active treatment. Conclusion: This case highlights the importance of considering sinister causes in patients presenting with non-traumatic pelvic fractures and the need for regular follow up for those patients investigated with unexplained weight-loss with inconclusive results, but with a high index of suspicion for malignancy.